Die Tagebücher des Grafen Egbert Belcredi 1850-1894 - Malíř, Jiří (2016)
The edition includes the diaries of Count Egbert Belcredi from 1850 until his death in 1894. Belcredi – who was the brother of Austrian Prime Minister Richard Belcredi (1865-67) – was an outspoken Conservative, with links both to the Bohemian States Rights Party and the early Christian Social movement in Vienna.Die Edition umfasst die Tagebücher des Grafen Egbert Belcredi von 1850 bis zu seinem Tode 1894. Belcredi, Bruder des österreichischen Ministerpräsidenten Richard Belcredi (1865-67), war ein kämpferischer Konservativer, der zwischen böhmischem Staatsrecht und den früheren christlichsozialen Strömungen in Wien pendelte...